Macropropagated plantlets in banana: Performance evaluation with suckers and tissue culture plants in Grand Naine and Nendran - Manju, P. R.; Pushpalatha, P. B. (Journal of Tropical Agriculture, 2021)
Macropropagation is a cost effective vegetative propagation technique, whereby 20-25 plants can be produced from a single corm in a matter of 3-4 months depending upon the variety. The technique involves the repression of apical meristem ultimately stimulating the regeneration of lateral meristem. The present study conducted at Banana Research Station, Kannara, attempted to evaluate the performance of macropropagated plantlets of banana varieties Grand Naine (AAA) and Nendran (AAB) compared to suckers and tissue culture plants. Macropropagated plantlets of both Grand Naine and Nendran responded as well as tissue culture plants and significantly better than suckers in terms of bunch weight, hands per bunch, fingers per bunch and finger weight. In Grand Naine, macropropagated plantlets recorded a bunch weight of 28.29 kg/plant, while in Nendran, it was 12.25 kg/plant. Sucker derived plants recorded 18.13 and 9.78 kg bunch weight in Grand Naine and Nendran respectively. An additional yield of 56% and 25% was obtained from macropropagated Grand Naine and Nendran respectively. Fruit quality in terms of TSS, acidity and shelf life remained on par among the treatments. No significant difference was observed among the treatments for days to bunching, days to harvest and crop duration.